Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.msea.2019.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Superior mechanical properties and deformation mechanisms of heterogeneous laminates under dynamic shear loading

Abstract: High-strain rate response of low C steel/304 stainless steel (SS) laminates was characterized by hat-shaped specimen using Hopkinson-bar technique at a strain rate of about 7×10 4 s-1. Better dynamic shear properties were observed in the laminates, compared to the plain low C steel plate and the plain 304 SS plate. The laminates were found to postpone the nucleation of adiabatic shear band (ASB) in the hard zone and to delay the propagation of ASB from the hard zone to the soft zone. The conventional maximum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…During laser pressure welding, the reaction layer underwent severe plastic deformation, resulting in the formation of heterogeneous laminates with dual-phases structure. Based on previous studies [29-31], the lamellar boundary strengthening originated from the nano-lamellar architecture in the heterogeneous laminates resulted in materials with superior mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…During laser pressure welding, the reaction layer underwent severe plastic deformation, resulting in the formation of heterogeneous laminates with dual-phases structure. Based on previous studies [29-31], the lamellar boundary strengthening originated from the nano-lamellar architecture in the heterogeneous laminates resulted in materials with superior mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…There are fewer studies on the dynamic deformation behavior and microstructure evolution of HS materials under high-speed-impact conditions [19,20]. He et al [35] characterized the dynamic deformation behavior of HS materials of low-carbon steel/304 stainless steel at high strain rates and found that the difference in hardness between the two components in HS materials is an important factor influencing the extension of the adiabatic shear band (ASB). However, the study is not relevant to titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Strain-rate strengthening effects, inertia effects, and thermal softening effects all affect the plastic deformation mechanisms and fracture forms of materials [35,[37][38][39][40]. Therefore, although some results of mechanical properties under quasi-static conditions have been available for HS materials, it is still impossible to predict their dynamic deformation behavior simply from the deformation behavior under quasi-static conditions.…”
Section: Introductionmentioning
confidence: 99%